Pathogenesis and Risk Factors for Cerebral Infarct After Surgical Aortic Valve Replacement. Issue 8 (August 2016) - Massaro, Allie; Messé, Steven R.; Acker, Michael A.; Kasner, Scott E.; Torres, Jose; Fanning, Molly; Giovannetti, Tania; Ratcliffe, Sarah J.; Bilello, Michel; Szeto, Wilson Y.; Bavaria, Joseph E.; Mohler, Emile R.; et al.
Abstract : Background and Purpose—: Stroke is a potentially devastating complication of cardiac surgery. Identifying predictors of radiographic infarct may lead to improved stroke prevention for surgical patients. Methods—: We reviewed 129 postoperative brain magnetic resonance imagings from a prospective study of patients undergoing surgical aortic valve replacement. Acute infarcts were classified as watershed or embolic using prespecified criteria. Results—: Acute infarct on magnetic resonance imaging was seen in 79 of 129 patients (61%), and interrater reliability for stroke pathogenesis was high (κ=0.93). Embolic infarcts only were identified in 60 patients (46%), watershed only in 2 (2%), and both in 17 (13%). In multivariable logistic regression, embolic infarct was associated with aortic arch atheroma (odds ratio [OR], 3.4; 95% confidence interval [CI], 1.0–12.0; P =0.055), old subcortical infarcts (OR, 5.5; 95% CI, 1.1–26.6; P =0.04), no history of percutaneous transluminal coronary angioplasty or coronary artery bypass graft (OR, 4.0; 95% CI, 1.2–13.7; P =0.03), and higher aortic valve gradient (OR, 1.3 per 5 mm Hg; 95% CI, 1.09–1.6; P =0.004). Watershed infarct was associated with internal carotid artery stenosis ≥70% (OR, 11.7; 95% CI, 1.8–76.8; P =0.01) and increased left ventricular ejection fraction (OR, 1.6 per 5% increase; 95% CI, 1.08–2.4; P =0.02). Conclusions—: The principal mechanism of acute cerebral infarction after aortic valve replacement is embolism. There are distinct factors associated with watershed and embolic infarct, some of which may be modifiable. Abstract : Supplemental Digital Content is available in the text.